Observational research in epidemic settings: a roadmap to reform - Marc Lipsitch; Nicholas Evans; Alexandra L Phelan; Stephany N Duda; Annette Rid; Colin J Carlson; Jennifer B Rosen; Natalie E Dean; John Barugahare; Maya B Mathur; Emily E Ricotta; Fausto A Bustos Carrillo; et al. (BMJ Global Health)
Observational studies are critical tools in clinical research and public health response, but challenges arise in ensuring the data produced by these studies are scientifically robust and socially valuable. Resolving these challenges requires careful attention to prioritising the most valuable research questions, ensuring robust study design, strong data management practices, expansive community engagement, and access and benefit sharing of results and research materials. This paper opens with a discussion of how well-designed observational studies contribute to biomedical evidence and provides examples from across the clinical literature of how these methods generate hypotheses for future research and uncover otherwise unattainable insights by providing examples from across the clinical literature. Then, we present obstacles that remain in ensuring observational studies are optimally designed, conducted and communicated.